Inter-departmental : copy of telegram received from Spanish Socialist Party (translated) - Lamoneda, Ramon, 1892-1971; Gillies, William
010-0139-001 Inter-Departmental THE LABOUR PARTY This form is for use when letters include subjects for attention by more than one department From (Organisation) Name of Sender Address Date of Letter Subject (ONE SUBJECT ONLY) Copy of telegram received from Spanish Socialist Party. (Translated) PT 186 Madrid 22 11 1400 W. Labour Party London Accept proof of our gratitude for your telegram. Be assured of our triumph. Fraternal greetings. Lamoneda Secretaire du Parti Socialiste. To Sir Walter Citrine. Handed from W. Gillies. Reply being dispatched Date August 12th, 1936. V.H.P. Co. 292/946/10/152